2D semimetal with ultrahigh work function for sub-0.1 V threshold voltage operation of metal-semiconductor field-effect transistors - Zhang, Tianjiao (2023)
Metal-semiconductor field-effect transistors (MESFETs) offer the advantages of efficient gate control and low power consumption due to the large junction capacitance. However, the strong Fermi-level pinning caused by the metal-induced gap states makes it a great challenge to build a high-quality Schottky junction with a large energy barrier and low leakage current. Moreover, the upper limit of the work function of conventional metals is around 5 eV, which prevents the formation of a wide depletion region and the reduction of power consumption. In this work, 2D semimetals with high work function have been used as the gate to fabricate 2D van der Waals MESFETs. Compared with PtSe2 and PdSe2, TiS2 with ultrahigh work function of 6.6 eV forms the largest Schottky barrier height with MoS2. And TiS2/MoS2 MESFETs display a sub-0.1 V threshold voltage owing to the large built-in potential and exhibit a small subthreshold swing of 73 mV/dec. The tuning of the channel carrier density from the back gate can further optimize the device performance and provide a strategy to build AND logic gate in a dual-gated transistor. Our work successfully demonstrates the use of high-work-function 2D semimetal to realize high-performance MESFET with low power consumption.